The Young Turks: Struggle for the Ottoman Empire, 1914-1918 / Feroz Ahmad - Ömer Taha Karabulut (Journal of Universal History Studies, 2022)
The powerful authority of the Committee of Union and Progress during World War I was undebatable. Evaluating and handling this theme as possessing the objective view of perspective and approaching through a rational horizon is inevitable. As a master of Turkish political history, Feroz Ahmad, exhibits the readers that how and why the demise period of the Ottoman Empire is significant in terms of the Committee of Union and Progress. Also, it ensures the reader to understand the powerful authority of the Committee of Union and Progress. "Feroz Ahmad The Young Turks: Struggle for the Ottoman Empire,1914-1918" has to be read on account of critical perspective. In this book review, the interpretations of the Feroz Ahmad analyzed in terms of critical and rational point of view. Moreover, review was supported by other sorts of academic sources. Every part of the book was examined differently that all of them written in different paragraphs. That is to say, this book review ensures the reader to understand what sort of situation that Ottomans were engaging in and how Feroz Ahmad responds to these questions in a radical way.